University-government-foundation collaboration on arms control and security policy in the United States from Truman to Trump - Matthew Evangelista (Peace Economics, Peace Science and Public Policy (PEPS), 2025)
The relationship between the United States government, private foundations, and university-based researchers working on peace and security policy has evolved over time. Since the end of World War II we can identify four main phases: (1) secret government funding into the 1960s; (2) a Golden Age of foundation support in the 1970s and 1980s; (3) decline of support after the end of the Cold War; (4) a revival of interest in the wake of the terrorist attacks of 11 September 2001, with government funding through the Pentagon's Minerva grants and new foundation support representing an unusual alliance between leftwing and realist critics of US military expansionism on the one hand and rightwing neoisolationists on the other. To illustrate these phases, the article draws, among others, on documents from Cornell and Harvard universities and materials from the Ford, MacArthur, and Koch foundations. It represents an idiosyncratic account, based in part on the author's experiences.
Keywords: 320; arms control; Cornell University; Ford Foundation; Harvard University; MacArthur Foundation; peace research